It’s c because if you look at it shows that it could do straight line
A * 4 = E........A = E / 4
B / 4 = E........B = 4E
C + 4 = E......C = E - 4
D - 4 = E.......D = E + 4
A + B + C + D = 100
(E/4) + (4E) + (E - 4) + (E + 4) = 100
E/4 + 6E = 100 ....multiply by 4
E + 24E = 400
25E = 400
E = 400/25
E = 16 <===
F(g(x)) = f(3x+2) = h(x)=9x^2+12x + 6
Note that (3x+2)^2 = 9x^2 + 12x + 4, which is almost, but not quite, equal to h(x).
Let's experiment. What if f(x) = x^2 + 2?
Then f(3x+2) = (3x+2)^2 + 2 = 9x^2 + 12x + 4 + 2 = 9x^2 + 12x + 6, which is the same as the given h(x).
Thus, f(x) is x^2 + 2.